Understanding the importance of cerebrovascular involvement in Kawasaki disease - Jung Sook Yeom; Jae Young Cho; Hyang-Ok Woo (Korean Pediatric Society, 2019)
Kawasaki disease (KD) is a systemic vasculitis in infants and young children. However, its natural history has not been fully elucidated because the first case was reported in the late 1960s and patients who have recovered are just now entering middle age. Nevertheless, much evidence has raised concerns regarding the subclinical vascular changes that occur in post-KD patients. KD research has focused on coronary artery aneurysms because they are directly associated with fatality. However, aneurysms have been reported in other extracardiac muscular arteries and their fate seems to resemble that of coronary artery aneurysms. Arterial strokes in KD cases are rarely reported. Asymptomatic ischemic lesions were observed in a prospective study of brain vascular lesions in KD patients with coronary artery aneurysms. The findings of a study of single-photon emission computed tomography suggested that asymptomatic cerebral vasculitis is more common than we believed. Some authors assumed that the need to consider the possibility of brain vascular lesions in severe cases of KD regardless of presence or absence of neurological symptoms. These findings suggest that KD is related with cerebrovascular lesions in children and young adults. Considering the fatal consequences of cerebral vascular involvement in KD patients, increased attention is required. Here we review our understanding of brain vascular involvement in KD.